SORPTION AND DESORPTION OF IRIDIUM BY COASTAL SEDIMENT: EFFECTS OF IRIDIUM SPECIATION AND SEDIMENT COMPONENTS - Dai X.; Chai Z.; Mao X.; Ouyang H. (My University, 2000)
The sorption and desorption behaviors of trace iridium in a coastal seawater-sediment system were studied via batch experiments. The linear sorption and desorption isotherms were observed in the range of 0.1-1.0 ng/ml Ir concentration, and the sorption-desorption process is irreversible. By using selective extraction method, the effects of Ir speciation in seawater and of sediment components on Ir sorption and desorption were investigated. The results indicate that the tetravalent Ir is easier to be sorbed by sediment than the trivalent iridium. Regarding the coastal sediment used in our study, the residue is the most important component for Ir sorption, whereas carbonate is not an effective absorbent component for iridium in sediment. The irreversible sorption-desorption process and very low desorption ability of iridium might lead to Ir enrichment on the sediment.
Keywords: IRIDIUM; SORPTION; DESORPTION; COASTAL SEDIMENT; SEAWATER; SPECIATION